Macro Role Playing Supports Adaptive Behaviour in Early Childhood: Permainan Peran Makro Mendukung Perilaku Adaptif pada Masa Kanak-kanak Awal - Qurrota A`yunin; Agus Salim (Universitas Muhammadiyah Sidoarjo, 2025)
Adaptive behaviour is fundamental for early childhood adjustment to school and social environments, requiring learning experiences that mirror real-life social situations. In the observed kindergarten context, role-playing activities had been implemented regularly, yet a focused analysis of their contribution to children’s adaptive behaviour had not previously been conducted. Existing literature highlights the developmental benefits of symbolic play, but specific evidence from this institutional setting remained limited. This study addresses that gap by examining how role-playing activities contribute to adaptive behaviour among children aged 5–6 years in a classroom environment. The research aims to analyse the contribution of the role-playing method to adaptive behaviour and identify the types of role play that produce positive outcomes. Using a descriptive qualitative approach, data were collected from 35 children, teachers, and parents through observation, interviews, and documentation, with source triangulation ensuring validity and interactive analysis guiding interpretation. Findings indicate that macro role-playing activities—such as simulations of shopping, transportation, museum visits, and professional roles—are associated with improved adjustment, social interaction, cooperation, emotional regulation, and basic problem solving. Supporting conditions include teacher facilitation, adequate play facilities, environmental support, and high child engagement, while limitations relate to equipment availability and individual differences. The study’s novelty lies in documenting context-specific implementation of macro role play using realistic props within everyday learning themes. These findings imply that structured experiential play can serve as a practical strategy for fostering adaptive behaviour in early childhood education settings. Highlights: Realistic simulations encourage cooperation, discipline, and rule-following during classroom activities. Structured scenarios facilitate emotional control and adjustment in new situations. Teacher guidance and supportive environments are essential for successful implementation. Keywords: Role Playing; Adaptive Behaviour; Macro Role Play; Early Childhood Education; Social Skills